Arsenic intoxication: general aspects and chelating agents - Bjørklund, Geir (Arch Toxicol, 2020)
Arsenic (As) is widely used in the modern industry, especially in the production of pesticides, herbicides, wood preservatives, and semiconductors. The sources of As such as contaminated water, air, soil, but also food, can cause serious human diseases. The complex mechanism of As toxicity in the human body is associated with the generation of free radicals and the induction of oxidative damage in the cell. One effective strategy in reducing the toxic effects of As is the usage of chelating agents, which provide the formation of inert chelator–metal complexes with their further excretion from the body. This review discusses different aspects of the use of metal chelators, alone or in combination, in the treatment of As poisoning. Consideration is given to the therapeutic effect of thiol chelators such as meso-2,3-dimercaptosuccinic acid, sodium 2,3-dimercapto-1-propanesulfonate, 2,3-dimercaptopropanol, penicillamine, ethylenediaminetetraacetic acid, and other recent agents against As toxicity. The review also considers the possible role of flavonoids, trace elements, and herbal drugs as promising natural chelating and detoxifying agents.